Interventions to Increase HIV Testing Uptake in Global Settings - Sundararajan, Radhika; Ponticiello, Matthew; Nansera, Denis; Jeremiah, Kidola; Muyindike, Winnie (Current HIV/AIDS Reports, 2022)
Purpose of Review: HIV testing is the critical first step to direct people living with HIV (PLWH) to treatment. However, progress is still being made towards the UNAIDS benchmark of 95% of PLWH knowing their status by 2030. Here, we discuss recent interventions to improve HIV testing uptake in global settings. Recent Findings: Successful facility-based HIV testing interventions involve couples and index testing, partner notification, and offering of incentives. Community-based interventions such as home-based self-testing, mobile outreach, and hybrid approaches have improved HIV testing in low-resource settings and among priority populations. Partnerships with trusted community leaders have also increased testing among populations disproportionally impacted by HIV. Summary: Recent HIV testing interventions span a breadth of facility- and community-based approaches. Continued research is needed to engage men in sub-Saharan Africa, people who inject drugs, and people who avoid biomedical care. Interventions should consider supporting linkage to care for newly diagnosed PLWH.
Keywords: HIV testing; Interventions; Global; Facility-based; Community-based